Light-weight Synchronous Java (SJL): An approach for programming deterministic reactive systems with Java - Motika, Christian; von Hanxleden, Reinhard (Computing, 2015)
A key issue in the development of reliable embedded software is the proper handling of reactive control-flow, which typically involves concurrency. Java and its thread concept have only limited provisions for implementing deterministic concurrency. Thus, as has been observed in the past, it is challenging to develop concurrent Java programs without any deadlocks or race conditions. To alleviate this situation, the Light-weight Synchronous Java (SJL) approach presented here adopts the key concepts that have been established in the world of synchronous programming for handling reactive control-flow. Thus SJL not only provides deterministic concurrency, but also different variants of deterministic preemption. Furthermore SJL allows concurrent threads to communicate with Esterel-style signals. As a case study for an embedded system usage, we also report on how the SJL concepts have been ported to the ARM-based Lego Mindstorms NXT system. We evaluated the SJL approach to be efficient and provide experimental results comparing it to Java threads.